PERANAN VISUM ET REPERTUM BAGI PENYIDIK JAKSA DALAM MELAKUKAN TUNTUTAN PIDANA KASUS PENGANIAYAAN DI PENGADILAN NEGERI SAMARINDA - Aris Wibowo (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT Visum Et Repertum in criminal proceedings, particularly in resolving the cases that related to a person’s soul or body, given the judges, prosecutors, public prosecutors and legal advisors only legally able to master it. Vise as documentary evidence, as well as other evidence which in article 184 of the criminal code that are not binding on the judge. This corresponds to a negative proof adopted in criminal procedural law in Indonesia, where elements of the judges conviction plays an important role in the resolution of a criminal case. The role of a Visum Et Repertum as documentary evidence greatly help the public prosecutor in the role in the manufacture of the demands that will be proposed upfront court, because in a Visum Et Repertum was contained or contains the testimony of a doctor who explains about what is seen and found in the examination of considered judges in decisions.Visum Et Repertum role of the prosecutor in conducting the criminal charges against cases of abuse, namely : as a substitute for evidence, provide input as the making charges by the public prosecutor in determining whether there is a criminal act or whether the accused guilty in the act.According to the body condition and health of the victim, then a Visum Et Repertum were given based on individual circumstances, for it was known five different Visum Et Repertum are Visum Et Repertum Tempat Kejadian Perkara, Visum Et Repertum Korban Hidup, Visum Et Repertum Jenasah, Visum Et Repertum Penggalian Jenasah, Visum Et Repertum Barang Bukti.            In Criminal Procedure Code and the role in legislation that others do not, there is one role which explicity mentions the post mortem, but safeguards that exist in the Criminal Code only mentions the statements of the experts are as stated in Pasal 1 Ayat 28, Pasal 120, Pasal 133, Pasal 184 and 184 KUHAP.  Keywords        :           children as victims of sexual crimes, child protection, and special protection to children vitims of sexual crimes